Formation of micro-cracks and recast layer during EDM of mild steel using copper electrodes - Khan, Ahsan Ali; Adesta, Erry Yulian Triblas; Mohammad , Yeakub Ali (International Islamic University Malaysia, 2011)
Abstract. The present paper reports on the influence of process parameters on formation of micro-cracks and recast layer on mild steel during EDM using a copper electrode. Surface quality was evaluated on the basis of work surface roughness, micro cracks and thickness of the recast layer. Current, pulse-on time, pulse-off time and voltage were the variable parameters for the present investigation. Micro cracks were found on the surface due to rapid heating and cooling of the surface during EDM. Micro cracks reduced in number and size when the surface was EDMed with a low current and a short pulse-on time. A layer of recast layer on the work surface was observed after EDM. The thickness of the recast layer was higher while a higher current together with a higher pulse-on time were used. It was concluded that in order to have a high quality surface it should be machined with lower values of current, pulse-on time and voltage.